The visual and audiovisual fiction narratives and art education of identity (European Journal of Child Development, Education and Psychopathology, 2019)
The article presents an analysis of the manner in which the visual narratives and audiovisual fiction offer a range of educational opportunities in order to be able to work on different problems of identity. Explores the possibilities that the artistic fiction has to generate multiple possible constructions of identities, for example, sexual and gender diversity among many other, favouring the empathic understanding of others and allowing a better relationship between human beings. We understand the narratives of fiction as an artistic expression builder of symbolic truths necessary for the understanding of the world and of people. They are therefore a means of artistic learning. Develops a theoretical analysis of the concept of fiction and is claimed as an educational tool and discusses examples of artists and experiences of identity and self-exploration through this type of practices. In conclusion, the article provides that the narratives of fiction contribute in a creative and effective way to the understanding of life forms and different identities, allow you to experiment on their own identity and, therefore, are a tool for learning about oneself and others.